A accountability educacional – arquétipo do estado gerencial e avaliador: os (des)caminhos da democracia e a preservação do establishment - Menezes, Hermeson Claudio Mendonça (2019)
This dissertation is materialized in the study of educational accountability as an archetype of the State Manager-Evaluator and how this mechanism is adopted, re-signified and replicated in the conjuncture of the (dis) ways of democracy as an instrument for the preservation of the establishment. In these analytical meanders, the concept of accountability, which is usually polysemic, is under intense scrutiny, with the aim of enriching the debate about it, understanding that every researcher is a historical subject with specific values ​​and interests, lacking scientific neutrality , which resulted in the approach to the historical-dialectical materialist theory, and as far as methodology is concerned, the work focuses on documentary-bibliographic research and content analysis. As a result of this approach, the dissertation develops an intense debate about the conceptualization and categorization of accountability, as its constituent devices - accountability, accountability and evaluation - connect in a historical (sociocultural and political-economic) process, in the field of power control and, more specifically, in social control. In analyzing educational accountability in historical dialeticity, considering the contradictions of educational policies and modernization projects under the aegis of capital, a course is traced whose structure involves an investigation of democracy and the Managerial-Evaluator State, considering them beacons for the implementation of educational policies to be justified by educational accountability, in close symbiosis with economic precepts of neoliberal normativity and Human Capital Theory. The educational accountability, when walking pari passu with these elements, makes possible the play of political-economic interests of the hegemonic groups (international and local), shaping democracy as an instrument of consolidation of the exclusionary order. It concludes that accountability falls within the role of the mechanisms that contribute to the reproduction of the conditions of production of the capitalist mode of production, being a fundamental part for the maintenance of the current order of social cohesion.